Perbedaan persiapan prakonsepsi ibu hamil primigravida yang mengalami kurang energi kronik dan tidak kurang energi kronik di Puskesmas Gianyar 1 periode Januari-Agustus 2017 - Adiputra, Ketut Pramana; Pinatih, IGN Indraguna; Seriani, Luh (E-Jurnal Medika Udayana; Vol 7 No 3 (2018): E-Jurnal Medika Udayana, 2018)
Maternal mortality is a complication of pregnancy that they even become a serious problem in Indonesia. There are several causes of maternal mortality in Indonesia, one of which is a pregnancy with chronic energy deficiency (CED). At the Gianyar 1 public health centre in 2017 obtained KEK high incidence in primigravidae. The purpose of this study to describe the preparation of preconception maternal and preconception preparation difference between pregnant women with KEK and pregnant women without CED in Gianyar 1 public health centre. This study used approach cross sectional with technique systematic sampling that involves primigravidae pregnant women who experience KEK as many as 20 samples and pregnant women who do not CED as many as 20 samples where all samples are recorded in Gianyar primary health centre 1 from January to August 2017The frequency of the highest maternal age of first pregnancy occurs in less than 20 years of age (55%). Most samples had normal BMI before becoming pregnant (67.5%). As many as 87.5% of the sample had no history of the disease before pregnancy. From the income before pregnancy obtained 57.5% of the samples have high income. Statistical analysis showed there are differences in the incidence of KEK views of BMI before pregnancy (P value ?0.05), there were no differences KEK incidence views of maternal history of the disease and the level of income before pregnancy. This research concludes that nutritional status can make pregnant woman have a CED status. Keywords: Primigravidae, CED, preconception